2006
DOI: 10.1159/000095087
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ulinastatin on Proliferation and Cytokine Release of Splenocytes from Rats with Severe Acute Pancreatitis

Abstract: Aim: To clarify the contributions of ulinastatin to cellular immune responses in vivo, we examined the functional alterations of splenocytes and quantitatively evaluated the effects of ulinastatin on the splenocyte function during experimental severe acute pancreatitis. Methods: Severe acute pancreatitis was induced in rats by retrograde injection of 3% sodium deoxycholate. Thirty minutes after induction of pancreatitis, the rats were randomly assigned to four groups, receiving either saline or 50,000 U/kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Maciejewski et al [7] showed that ulinastatin administration increased the survival rate in experimental animals of AP. Furthermore, previous studies [6, 8] have shown that ulinastatin can inhibit the expression of tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β), and increase the levels of IL-2 and IL-10. The studies on the mechanism of the anti-inflammatory effect of ulinastatin have mainly been focused on the roles of these cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Maciejewski et al [7] showed that ulinastatin administration increased the survival rate in experimental animals of AP. Furthermore, previous studies [6, 8] have shown that ulinastatin can inhibit the expression of tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β), and increase the levels of IL-2 and IL-10. The studies on the mechanism of the anti-inflammatory effect of ulinastatin have mainly been focused on the roles of these cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical outcome of anti‐proteolytic drug trials, and the mechanism of drug action deduced thereof, remains controversial . The potential of ulinastatin in treating pancreatitis has been demonstrated extensively in conditions such as post‐endoscopic retrograde cholangiopancreatography pancreatitis, experimental acute pancreatitis, and chronic pancreatitis . In addition to blocking proteases, there is growing evidence that ulinastatin might play a role in preventing progressive inflammation of the pancreas, irrespective of the associated cause …”
Section: Introductionmentioning
confidence: 99%
“…Previous in vivo studies have shown that ulinastatin can inhibit the expression of nuclear factor‐κB (NF‐κB), tumor necrosis factor‐α (TNF‐α), and interleukin‐6 (IL‐6), and increase the levels of IL‐2, IL‐10, and interferon‐γ . These cytokines play important roles in the initiation and amplification of inflammatory responses during pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…The immune indices in patients, including T lymphocyte counts, T lymphocyte function, and cytokine pro-duction, in the perioperative period were recovered to different extents after the application of UTIs. Consequently, it has been suggested that the UTI improves immune function (Sato et al, 2002;Ma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%